2013
DOI: 10.1016/j.neuro.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

A single neonatal exposure to perfluorohexane sulfonate (PFHxS) affects the levels of important neuroproteins in the developing mouse brain

Abstract: A single neonatal exposure to perfluorohexane sulfonate (PFHxS) affects the levels of important neuroproteins in the developing mouse brain. , 37: 190-196 Neurotoxicology AbstractPerfluorohexane sulfonate (PFHxS) is an industrial chemical and belongs to the group of perfluorinated compounds (PFCs). It has recently been shown to cause developmental neurobehavioral defects in mammals. These compounds are commonly used in products such as surfactant and protective coating due to their ability to repel water-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 63 publications
0
20
0
3
Order By: Relevance
“…It is also consistent with our individual-level finding that some of the participants had a large positive mean change score for PFHxS between visits. The hazards of PFHxS could include developmental neurotoxicity (Lee and Viberg, 2013) or endocrine-disrupting potential (Kjeldsen and Bonefeld-Jorgensen, 2013; Long et al, 2013; Wen et al, 2013), so it is important to determine whether there is a new source of PFHxS exposure and to further characterize this compound’s relevance for human health. The possible change in trajectory of PFHxS suggested at the population level but not corroborated by most individual trajectories could also be a result of aggregation bias.…”
Section: Discussionmentioning
confidence: 99%
“…It is also consistent with our individual-level finding that some of the participants had a large positive mean change score for PFHxS between visits. The hazards of PFHxS could include developmental neurotoxicity (Lee and Viberg, 2013) or endocrine-disrupting potential (Kjeldsen and Bonefeld-Jorgensen, 2013; Long et al, 2013; Wen et al, 2013), so it is important to determine whether there is a new source of PFHxS exposure and to further characterize this compound’s relevance for human health. The possible change in trajectory of PFHxS suggested at the population level but not corroborated by most individual trajectories could also be a result of aggregation bias.…”
Section: Discussionmentioning
confidence: 99%
“…The BGS have shown to be sensitive to toxic insults by xenobiotics such as polybrominated diphenyl ethers (PBDEs), polychlorinated biphenyls (PCBs), perfluorinated compounds (PFCs), pharmaceuticals, nicotine and bisphenol A (Eriksson, 1998;Eriksson et al, 2000;Johansson et al, 2008Johansson et al, , 2009Lee and Viberg, 2013;Viberg et al, 2006Viberg et al, , 2008bViberg et al, , 2011Viberg et al, , 2013Viberg et al, , 2014Viberg and Lee, 2012); and we have previously seen that certain of these xenobiotics affect the level of neuroprotein expression when exposed during this critical phase. Also, previous studies on pyrethroids and organochlorines have shown to cause developmental neurotoxicity in mice, manifested as deranged spontaneous behavior and changes in muscarinic acetylcholine receptor density in the brain, when neonatally exposed (Ahlbom et al, 1994;Eriksson et al, 1992Eriksson et al, , 1993Talts et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, animal and human studies have now linked PFC exposure with developmental toxicity [27], neurotoxicity [28], reproductive toxicity [29], cardiovascular toxicity [26], metabolic dysregulation [30], development of arthritis [31], carcinogenesis [32], and immunotoxicity [33]. There has been minimal research exploring strategies to eliminate PFCs [34].…”
Section: Introductionmentioning
confidence: 99%